The value of radiotherapy in the treatment of aged-related macular degeneration (AMD) - Zarzycka, Małgorzata; Ziółkowska, Ewa; Słonina, Aleksandra (Contemporary Oncology/Współczesna Onkologia, 2007)
Age-related macular degeneration (AMD) is the leading cause of blindness in patiens older then 65 years. There are two forms of AMD: exudative ”wet” and nonexudative ”dry”. Most of the lesions are not amenable to laser therapy because of their vicinity to the fovea. Earlier studies suggested that radiotherapy may inhibit further loss of visual acuity but following studies rendered contradictory results. In recent years, treatment of beningn disease has again attracted the interest of the radiation oncology community in the Western part of the world. Radiotherapy has been given successfully to patiens suffering from a wide variety diseases and AMD is one of them. The present article extensively reviews the clinical studies to define the role of radiotherapy in the treatment of AMD.